Challenges of collaborative economy ventures in Colombia - Gómez Navarro, María Victoria
The recession, the fall of powerful empires and the strong entry of technology, have caused profound changes in the economic dynamics, making every time there are other revolutionary recovery alternatives, starting from lines that can become very influential because of the great impact it produces and the number of people that benefit, as is the case of the collaborative economy, which has permeated multiple scenarios, making the traditional sectors of the economy reinvent. This phenomenon has not been foreign to Colombia, and the state of the art and the examples of reference, are registered the challenges to which the collaborative economy ventures in Colombia are exposed. The country, being able to draw conclusions from social, technological, environmental and legal contexts.